2020
DOI: 10.1186/s13756-020-0703-3
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenemase-producing Enterobacteriaceae circulating in the Reunion Island, a French territory in the Southwest Indian Ocean

Abstract: Background: The spread of carbapenemase-producing Enterobacteriaceae (CPE) in the Southwest Indian Ocean area (SIOA) is poorly documented. Reunion Island is a French overseas territory located close to Madagascar and connected with Southern Africa, Indian sub-continent and Europe, with several weekly flights. Here we report the results of the CPE surveillance program in Reunion Island over a six-year period. Methods: All CPE were collected between January 2011 and December 2016. Demographics and clinical data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…In this study, 57% of the carbapenemase-producing strains were sensitive to tigecycline. The rates found are close to those reported by a study conducted in Reunion Island, a French territory in the Southwest Indian Ocean, which found a susceptibility rate of 67% to tigecycline of CPE strains [11]. A study conducted in Tunisia in a major burns unit found that for CPE, the lowest resistance rates were recorded for tigecycline (43%) and fosfomycin (33%).…”
Section: Discussionsupporting
confidence: 84%
“…In this study, 57% of the carbapenemase-producing strains were sensitive to tigecycline. The rates found are close to those reported by a study conducted in Reunion Island, a French territory in the Southwest Indian Ocean, which found a susceptibility rate of 67% to tigecycline of CPE strains [11]. A study conducted in Tunisia in a major burns unit found that for CPE, the lowest resistance rates were recorded for tigecycline (43%) and fosfomycin (33%).…”
Section: Discussionsupporting
confidence: 84%
“…Our results showed that pKPC2 was the most prevalent carbapenemase-encoding plasmid among the clinical Enterobacterales isolates in CaPES. These plasmids are largely found in K. pneumoniae, E. coli, and E. cloacae, which also were the most prevalent carbapenemase-encoding plasmid-harboring species reported in other surveillance studies (31,32), showing that those are major reservoirs. Although KPC-2 has been documented on diverse plasmids and is known to undergo frequent recombination events (33), we uncovered a single plasmid that moves as a discrete and intact unit among diverse strains and species.…”
Section: Discussionmentioning
confidence: 64%
“…In the same year, a patient returning from Mauritius was found to be carrying a carbapenemase-producing K. pneumoniae isolate with the bla NDM-1 and bla OXA-181 genes ( 18 ). From 2011 to 2016, 61 Enterobacterales from 53 patients on Reunion Island were identified to have carbapenem resistance ( 19 ). Among them, 13 E. coli belonging to eight STs (ST10, ST12, ST167, ST349, ST354, ST405, ST410, ST1284) were recovered.…”
Section: Resultsmentioning
confidence: 99%